Keberkesanan ekstrak hylocereus polyrhizus merendahkan lipid serum dan aras MDA-TBAR hati tikus teraruh hiperkolesterolema - Halimah Abdullah Sani,; Asmazila Baharoom,; Muhammad Azam Ahmad,; Isma Illyani Ismail, (Universiti Kebangsaan Malaysia, 2009)
Hypercholesterolemia is often associated with changes in lipid profile and an increase in lipid peroxidation level. In this study, the effects of peel and flesh aqueous extracts of Hylocereus polyrhizus (HP) fruit on serum total cholesterol and triglyceride (TG) and liver malondialdehyde (MDA-TBAR) levels in hypercholesterolemic rats were evaluated. Male Sprague dawley rats were induced into hypercholesterolemia by giving rat chow diet plus 15% pure ghee for 8 weeks and forced-fed with 0.02 g cholesterol in 0.5 ml ghee twice a week. Rats were then treated with 300 mg/kg (body weight) of peel and flesh extracts of H. polyrhizus fruit via force feeding for 10 days. The results show that total cholesterol level was reduced significantly (p<0.05) in both hypercholesterolemic groups treated with peel and flesh extracts by 51.36% and 43.53% respectively. The TG level showed a reduction by 42.98% in peel extract treated group and 38.0% in rats treated flesh extract. The increase in liver MDA-TBAR level was inhibited by 56.85% in group treated with peel extract (p<0.05) whereas the flesh extract only caused a slight decrease by 10.27% compared to the untreated diabetic group. In this study, the peel aqueous extract of H. polyrhizus showed a greater effect than the flesh extract. This could be due to the higher content of antioxidant betacyanin in the fruit peel than in the flesh. Hylocereus polyrhizus aqueous extract have the potential in lowering the lipid profile and liver MDA-TBAR level in hypercholesterolemic rats.